Atomic Physics - Foot, C.J (Oxford master series on atomic, optical and laser physics, 2004)
This book is primarily intended to accompany an advanced undergraduate course in atomic physics. However, the elementary atomic physics covered in the early chapters should be accessible to undergraduates when they are first introduced to the subject. The book describes some of the latest advances and the applications to Bose-Einstein condensation of atoms, matter-wave interferometry and quantum computing with trapped ions. To complement the usual quantum mechanical treatment of atomic structure the book strongly emphasizes the experimental basis of the subject, especially in the later chapters.